Padrões de beleza na publicidade das revistas femininas (dos anos 1960 aos dias atuais) - Gentil, Gisele Mello (2009)
This project has the goal to research the influence of women´s magazines on the making up of the present female beauty patterns. For doing so, the research starts from an analysis of the beauty patterns in 1960´s, 1970´s, 1980´s, 1990´s and 2000´s run in the advertising of CLAUDIA and NOVA magazines published by Abril publisher, building up the corpus of this research. A special attention is given to the use of editing softwares to correct images such as Photoshop, due to the fact of its extensive use in post production of women´s advertising photos run in the analyzed magazines; fact incisively proved through interviews with professionals from PLAYBOY and NOVA magazines that complemented the research. From the theoretical point of view, this research is based upon Umberto Eco, Georges Vigarello and Nancy Etcoff works on the history of beauty; the work of Lucia Santaella on the approach of the forthcoming post human phenomenon; to support the ideas of analysis on the politics of the body in the context of the digital culture the works of Mark Dery, Nízia Villaça and Paula Sibilia were used. Through the theory that the pattern of present female beauty is part of an image, women´s appearance, their activities and other elements such as colors and images were analyzed in the publicity ads. The analysis show that the exposure to the advertising images of women mechanically perfect, changed and corrected through the use of editing images softwares, impose to real women a naturally impossible beauty pattern leading them to search for solutions to make their bodies into what the Photoshop makes in advertising. At the end, based upon the corpus of the research and in the light of its bibliography, it is concluded that the present beauty pattern became a stereotype and it suffers the influence of the means of communication and the new technological scenery and it is ruled by the images projected in advertising. Those are images that go through several interventions of editing and correcting softwares that lead several women to submit themselves to surgical and chemical interventions with the purpose of drawing closer to the image shown on the means of communication